Critical assessment of gassing-in methods for measuring k(l)a in fermentors - Linek, V; Sinkule, J; Benes, P (Biotechnology and bioengineering, 1991)
The reliability of dynamic measurement methods of k(l)a in fermentors using a step oxygen concentration change in the feed gas was tested. The tests were performed both for the original variant using the nitrogen right harpoon over left harpoon air exchange and the newly presented variant using the oxygen-enriched air (27 vol % O(2)) --> air exchange. The testing consisted in comparing k(l)a values determined from these methods with values determined from the steady-state Na(2)SO(3) feeding method and the dynamic pressure method, the reliability of which was proven earlier. The measurements were done in water (coalescent batch) and in 0.5M Na(2)SO(4) solution with and without the addition of 1 wt % carboxymethylcellulose (noncoalescent batches). It was found that in noncoalescent liquids the methods tested give extremely low k(l)a values (as low as 15% of the correct value). The methods are defective in principle irrespective of the gases used for exchange.